The Inflammatory Role of Platelets via Their TLRs and Siglec Receptors - Cognasse, Fabrice; Nguyen, Kim Anh; Damien, Pauline; McNicol, Archibald; Pozzetto, Bruno; Hamzeh-Cognasse, Hind; Garraud, Olivier (Frontiers in Immunology, 2015)
Platelets are non-nucleated cells that play central roles in the processes of hemostasis, innate immunity, and inflammation; however, several reports show that these distinct functions are more closely linked than initially thought. Platelets express numerous receptors and contain hundreds of secretory products. These receptors and secretory products are instrumental to the platelet functional responses. The capacity of platelets to secrete copious amounts of cytokines, chemokines, and related molecules appears intimately related to the role of the platelet in inflammation. Platelets exhibit non-self-infectious danger detection molecules on their surfaces, including those belonging to the “toll-like receptor” family, as well as pathogen sensors of other natures (Ig- or complement receptors, etc.). These receptors permit platelets to both bind infectious agents and deliver differential signals leading to the secretion of cytokines/chemokines, under the control of specific intracellular regulatory pathways. In contrast, dysfunctional receptors or dysregulation of the intracellular pathway may increase the susceptibility to pathological inflammation. Physiological vs. pathological inflammation is tightly controlled by the sensors of danger expressed in resting, as well as in activated, platelets. These sensors, referred to as pathogen recognition receptors, primarily sense danger signals termed pathogen associated molecular patterns. As platelets are found in inflamed tissues and are involved in auto-immune disorders, it is possible that they can also be stimulated by internal pathogens. In such cases, platelets can also sense danger signals using damage associated molecular patterns (DAMPs). Some of the most significant DAMP family members are the alarmins, to which the Siglec family of molecules belongs. This review examines the role of platelets in anti-infection immunity via their TLRs and Siglec receptors.